Molecular characterisation of methicillin-resistant Staphylococcus aureus and Staphylococcus pseudintermedius in cats, dogs and pet owners in a Veterinary Hospital - Afshar, Mohammad Farzad (2022)
The genus staphylococcus includes opportunistic pathogens such as methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus pseudintermedius (MRSP), which are of public health importance. This study aimed to investigate the presence of MRSA and MRSP bacteria in dogs, cats, and their owners in University Veterinary Hospital, UPM and understand the possible zoonotic transmission of these pathogens. Samples were collected from 150 dogs, 100 cats and 100 pet owners that visited the University Veterinary Hospital, Faculty Veterinary Medicine, UPM, and dogs and cats from animal pounds. The obtained bacterial cultures were phenotypically and genotypically identified using selective agar, a series of biochemical tests and Polymerase Chain Reaction (PCR) for species and methicillin resistance confirmation. Staphylococcus pseudintermedius and Staphylococcus aureus were present in 17 (4.85%), and seven (2%) samples, respectively. One of these isolates (2%) was identified as MRSA, one (1.3%) isolate from pet dogs, one (2%) from pet cats and one (1%) from pet owners were confirmed to be MRSP. Antimicrobial susceptibility tests were performed using the standard disk diffusion method. Two (50%) isolates (one MRSA and one MRSP) showed multidrug resistance, while the other two MRSP isolates showed resistance against one and two antimicrobial agents. Multilocus sequence typing was performed by amplifying seven housekeeping genes, Sanger’s sequencing and using PubMLST for sequence type assignment. ST789 was assigned for S. aureus (76_C_M). S. pseudintermedius (65_C_F) isolated from a cat was assigned as ST 2296, which is related to clonal complex 45 and the other S. pseudintermedius (18_W_M) isolated from a pet owner (ST 2297) is a corresponding sequence type of 2296. A singleton was one of S. pseudintermedius (ST 2298) (88_D_F) isolates from a dog. Staphylococcal protein A (spa) typing for both MRSA and MRSP isolates was performed and typed. Only one MRSA isolate was typable as spa type t091, and the rest of the isolates were not typable. Staphylococcal Cassette Chromosome mec (SCCmec typing) typing was performed using multiplex PCR. The sole MRSA identified as SCCmec type V and MRSP isolates were type II and VII. The risk factors associated with the spread of staphylococci were investigated using a questionnaire distributed to 125 pet owners. Having close contact with animals like allowing them to lick face and having other animals had a significant association with carriage of staphylococci in this study. However, due to a small number of isolates, other factors were not significantly associated with carriage of our target organisms; therefore, there is a need to further study the risk factors that are associated with carriage of staphylococci the future. In brief, both MRSA and MRSP that were detected in the current study were multidrug resistant and molecularly related to other Southeast Asian countries. The findings from this study have brought new insights into the current status of antimicrobial resistance and molecular characteristics of both S. aureus and S. pseudintermedius isolated from dogs and cats in Malaysia.